Pengaruh Kualitas Layanan dan Nilai Pelanggan terhadap Kepuasan Nasabah serta Kepercayaan Merek pada Perusahaan Asuransi Jiwa - Nina Tarja Halonen; Usep Suhud; Mohamad Rizan (Fakultas Ekonomi Universitas Negeri Jakarta, 2020)
This research aims to determine the effect of service quality and customer value towards brand trust on life insurance companies. The subject in this research are customers who have active life insurance policy at life assurance companies. The sampling technique was purposive sampling, generating 250 respondents. This research uses quantitative methods. Data collection was carried out by distributing questionnaires using a 5-point Likert scale with 220 total valid responses. Data analysis method used in this study is Structural Equation Modeling (SEM) using Amos version 24. The results showed that service quality had a positive and significant effect on customer satisfaction, customer value had a positive and significant effect on customer satisfaction, customer satisfaction had a positive and significant effect on brand trust, service quality had a positive and significant effect on brand trust, customer value had a positive and significant effect on brand trust.